Desain Pembelajaran Menggunakan Tessellation Berbasis Pendekatan Saintifik pada Materi Translasi dan Refleksi - Widiawati Widiawati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2019)
The purpose of this study was to determine the role of tesselation in translational and reflection material in developing students' mathematical communication based on a scientific approach. The research method uses design research type validation study involving 30 students of class VII SMP 9 Palembang. The research process produces learning trajectory which contains a series of learning processes in two activities, namely scientific on translational material and scientific on reflection material. Every scientific activity consists of observing, asking, reasoning, trying, and forming networks. The results of the study showed that by providing learning material through a scientific approach, the role of tesselations could help students to carry out mathematical communication so that they could identify translational and reflection material. Therefore, students can understand the concepts of translation and reflection and solve problems related to the material. In conclusion, learning using tessellation with a scientific approach effectively helps students understand the concepts of translation and reflection. Through activities such as observing, asking, reasoning, trying, and forming networks Keywords: Mathematical Communication, Scientific Approach, Tessellation